Reassessing Mass Media Reporting as Criminal Evidence in Indonesia toward Social Media Justice - Arief Setia Nugroho; Amad Sudiro; Hery Firmansyah (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2026)
The criminal justice system enforces legal norms and delivers justice by relying on legally admissible evidence as the foundation of judicial decision making. In Indonesia, the legislature enacted Law No. 20 of 2025 to reform the evidentiary system, replace the previous Criminal Procedure Code, and expand the categories of admissible evidence under Article 235 from five to eight types, including the formal recognition of electronic evidence. This reform accommodates the increasing role of digitalisation in legal processes and integrates contemporary forms of evidence into the criminal justice framework. This study analyses the implications of the evidentiary reform and examines the interpretation of mass media reporting as a source of factual information in criminal proof. The research applies a normative legal method, employs conceptual and socio legal approaches, and conducts qualitative descriptive analysis of statutory regulations and legal doctrines. The findings demonstrate that, first, mass media reporting disseminated through digital platforms qualifies conceptually as electronic documents within the expanded evidentiary framework. Second, such reporting functions as a supplementary evidentiary source when it fulfils the principles of legality, authenticity, verification, and relevance. Third, despite this potential contribution, mass media reporting lacks independent probative value and therefore cannot serve as conclusive evidence in criminal proceedings.